2002
DOI: 10.1021/cm010690l
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Ultralow Dielectric Constant Organosilicates Templated by Triblock Copolymers

Abstract: Triblock polymers, poly(ethylene oxide-b-propylene oxide-b-ethylene oxide) (PEO-b-PPO-b-PEO), are used as molecular templates in poly(methyl silsesquioxane) (MSQ) matrixes to fabricate nanoporous organosilicates for low dielectric constant applications. The results show that aggregation of block copolymers in the MSQ matrix can be prevented with the fast solvent evaporation which accompanies spin casting. Solid-state NMR shows that the triblock copolymer microphase-separates from the MSQ during a curing step, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
109
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 24 publications
2
109
0
Order By: Relevance
“…This expected reduction in the dielectric constant of nanoporous systems has been experimentally demonstrated both in polymeric materials and in other systems, such as silica [121][122][123] or organosilicates [124][125][126][127][128][129]. The results concerning the latter will be described briefly below for comparison with the results obtained in polymeric materials.…”
Section: Dielectric Propertiesmentioning
confidence: 70%
See 2 more Smart Citations
“…This expected reduction in the dielectric constant of nanoporous systems has been experimentally demonstrated both in polymeric materials and in other systems, such as silica [121][122][123] or organosilicates [124][125][126][127][128][129]. The results concerning the latter will be described briefly below for comparison with the results obtained in polymeric materials.…”
Section: Dielectric Propertiesmentioning
confidence: 70%
“…Organosilicates are also promising materials for low-k dielectrics because of their intrinsic hydrophobic behavior and the high thermal stability of the solid matrix [124][125][126][127][128][129]. Yang and coworkers [124,125] produced poly(methyl silsesquioxane) (MSQ) nanoporous organosilicate films (thicknesses of 0.3-0.8 lm) with pore sizes between 2 and 6 nm, porosities from 30% to 50%, and k values from 2 to 1.5 (lower values than that of the solid, k s % 2.8).…”
Section: Dielectric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al 46 reported a now widely accepted view that trapped water and surface hydroxyl ions. etc.…”
Section: Fig 5 Nanoindentation Studies Of Zeolite Films: Hardness Amentioning
confidence: 99%
“…Other material formulations intentionally incorporate porosity into the material during processing. 54,55 The porous regions have a dielectric constant of 1.0, thereby lowering the overall dielectric constant of the material. Of course, the quintessential low-k material is air; as a result, studies have been undertaken that generate or incorporate air gaps between metal layers in device structures.…”
Section: The Early Years: 1902 To 1977mentioning
confidence: 99%